2019
DOI: 10.1002/hep4.1421
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Trial of Withdrawal and Reinstitution of Ursodeoxycholic Acid in Pediatric Primary Sclerosing Cholangitis

Abstract: Ursodeoxycholic acid (UDCA) is commonly used to treat several liver disorders in adults and children, including primary sclerosing cholangitis (PSC) for which it is not U.S. Food and Drug Administration approved. UDCA treatment has an uncertain impact on disease outcomes and has been reported in high doses to be associated with worse outcome in adults with PSC. In this context, controlled withdrawal and reintroduction of UDCA in children with PSC were studied. Prior to study initiation, participants were requi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 38 publications
1
13
0
Order By: Relevance
“…Notably, it took 6 years at 12 large centers to enroll 22 children to complete a 12‐week study protocol, in large part because of unwillingness of families to stop UDCA. ( 23 ) Here, we show the lack of effectiveness of the two major therapies used in pediatric PSC, which were comparable to observation. The clinical equipoise of existing strategies for PSC justifies the safety of placebo‐controlled trials, and the high rates of spontaneous biochemical normalization demands them.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Notably, it took 6 years at 12 large centers to enroll 22 children to complete a 12‐week study protocol, in large part because of unwillingness of families to stop UDCA. ( 23 ) Here, we show the lack of effectiveness of the two major therapies used in pediatric PSC, which were comparable to observation. The clinical equipoise of existing strategies for PSC justifies the safety of placebo‐controlled trials, and the high rates of spontaneous biochemical normalization demands them.…”
Section: Discussionsupporting
confidence: 84%
“…Controlled withdrawal of UDCA from children on chronic therapy with normal biochemistry showed that most did not experience a biochemical flare. ( 23 ) One‐third of patients in the study maintained a completely normal GGT, raising the question of whether they were receiving any therapeutic benefit from UDCA or whether they would have initially normalized biochemistry spontaneously.…”
mentioning
confidence: 99%
“…which showed approximately 1/3 of patients had no significant change in labs with withdrawal of UDCA, while 1/3 of patients met criteria for a disease flare with withdrawal of UDCA, though long term differences in these 2 subsets were not reported (103). This suggests that there may be a subset of patients who have biochemical evidence of UDCA response, and that those patients may have improved outcomes arguing for continuation of UDCA in these patients.…”
Section: Ursodeoxycholic Acid (Udca)mentioning
confidence: 97%
“…Cholestasis may be caused by either intrahepatic or extrahepatic dysfunction ( 1 ), and may lead to a range of clinical hepatobiliary diseases, such as liver failure, hepatobiliary malignancy and bile fibrosis, cirrhosis ( 2 ). Ursodeoxycholic acid (UDCA) is currently the only treatment approved by the US Food and Drug Administration for the treatment of patients with cholestasis ( 3 ). However, according to the Primary Biliary Cholangitis Treatment and Management Guidelines from the British Society of Gastroenterology from 2018, oral UDCA is not an ideal therapeutic option as it may aggravate liver injury and one-third of patients are unresponsive to it ( 4 , 5 ).…”
Section: Introductionmentioning
confidence: 99%